La crise du Covid, un révélateur de la différenciation genrée des pratiques marchandes - Nicolas Lebrun; Corinne Luxembourg (Métropoles)
The frequentation of places of commerce responds to gendered logics. The methods of consumption of men and women differ by their temporality, the nature of the demand, places frequented and purchasing power. Living standards, family structures and greater job insecurity make the female population more exposed to the vagaries of uncontrolled consumption. Based on the results of several field surveys carried out during the health crisis, this article proposes to explain how the analysis of consumption practices during the different phases of lockdown and reopening makes it possible to refine this reading of the gendered use of merchant places. We assume that this crisis, through the economic, family and professional reorganisations it has caused, has reinforced the gendered dimension of the relationship of individuals to places of consumption. The article allows us to see, using the Covid crisis as a revelation, how the gendered differentiation of consumption practices evolves.